TANGGUNG JAWAB ILMU PENGETAHUAN: Pergulatan Antara Kaum Pragmatis dan Puritan-Elitis - Ahmad Takrifin (IAIN Pekalongan, 2010)
The emergence of discovery in science is always followed by two attitudes: (1) ethical, the development of science is accord with ethical values and benefit; and (2) free values, since its emergence, science is meant to develop itself. The former is promoted by pragmatism group viewing that science is not only to find the truth, but also benefit human life to solve many problems in their life. The latter, on the other hand, is promoted by puritan-elite group viewing that the aim of science is to find the truth and the objective explanation of everything. Therefore, science cannot submit to other authority out of itself. To bridge these two tendencies, the synthesis understanding of the context of discovery and the context of justification wherein the science emerges and develops is needed.